Pengembangan lembar kerja siswa (LKS) matematika untuk kelas VII Sekolah Menengah Pertama (SMP) pada materi aritmatika sosial - Syahputri, Iga; Sari, Riska Novia (Karoteh Utama, 2021)
The main objective of this research is to develop a valid Student Worksheet (LKS) in mathematics, mainly focusing on social arithmetic. The method applied in this study is the research and development approach, involving three crucial stages: definition, design, and development. A validation questionnaire was used as the research instrument. Based on the results of validity tests conducted by three validators, after undergoing a process of revisions and improvements, an average validation score of 3.36 was obtained for the mathematics LKS, categorized as